Online-only publishers are here to stay, and will continue to work closely with the ICZN - Moylan, Elizabeth; Harold, Simon; Harris, Philippa; Foote, Christopher; Arme, Chris; Minelli, Alessandro; Kowalczuk, Maria; Black, Caroline (Zootaxa, 2014)
BioMed Central is a Science, Technology and Medical publisher of online, open access journals. We have always endeavoured to ensure that our journals adhere to the norms of the research communities we serve (Knapp et al., 2011; Krell 2012; Sands & Moylan 2012). We were therefore somewhat bewildered by the tone of the piece from Dubois et al. (2013) criticising online-only journals, specifically our interpretation of the International Code of Zoological Nomenclature (the Code) on criteria for publication for nomenclatural purposes (ICZN 1999) prior to the 2012 Amendment to the International Commission on Zoological Nomenclature (ICZN 2012a,b,c). We responded to this in our recent blog (Harold et al., 2013).